Soroprevalência de anticorpos contra o vírus da Hepatite A entre estudantes de escolas públicas em duas cidades do Triângulo Mineiro - Gonçalves, Alana Arantes Santos (2012)
Introduction: in several developing countries, the endemicity patterns of hepatitis A (HA) have changed from high to intermediate and from intermediate to low, as a result of improvements in sanitation and hygiene conditions. Adolescents and adults without immunity are vulnerable to this infection, when the disease is more severe than when acquired during childhood. Objectives: to determine the seroprevalence of immunity against hepatitis A virus (HAV) among public school students of two cities located in the state of Minas Gerais, in the Southeastern region of Brazil, and to associate it with their conditions socioeconomic and environmental. Methods: antibodies anti-HAV seroprevalence was determinate (ELISA method) in 487 students, aged 7-18 years. Students were enrolled in public schools in the cities of Uberlândia (604,013 inhabitants) and Limeira do Oeste (6,890 inhabitants), and were divided according to sex and age. Their socioeconomic and environmental data also were collected. Results: total anti-HAV was positive in 62/304 (20.4%) students in Uberlândia, with a higher frequency (p=0.05) among those in peripheral schools (38/150; 25.3%) than others in central schools (24/154; 15.6%), and in 24/183 (13.1%) students in Limeira do Oeste. Seroprevalence increased with age and was similar between boys and girls. The multivariate analysis showed no statistically significant correlation between seropositivity and socioeconomic and environmental conditions. Conclusions: the low seroprevalences of immunity against HA found in the population evaluated reveal the need to implement vaccination strategies against this infection.